2011
DOI: 10.1371/journal.pone.0025493
|View full text |Cite
|
Sign up to set email alerts
|

Type-Specific HPV Prevalence in Cervical Cancer and High-Grade Lesions in Latin America and the Caribbean: Systematic Review and Meta-Analysis

Abstract: BackgroundCervical cancer is a major public health problem in Latin America and the Caribbean (LA&C), showing some of the highest incidence and mortality rates worldwide. Information on HPV type distribution in high-grade cervical lesions (HSIL) and invasive cervical cancer (ICC) is crucial to predict the future impact of HPV16/18 vaccines and screening programmes, and to establish an appropriate post-vaccinal virologic surveillance. The aim was to assess the prevalence of HPV types in HSIL and ICC in studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
63
2
11

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 81 publications
28
63
2
11
Order By: Relevance
“…In overall summarized of our study found that the HPV prevalence ratio in HSIL was not different from the other in analogous previous studies (Bhatla et al, 2008;Ciapponi et al, 2011;Correnti et al, 2011;Mateos et al, 2011), although the multiple HPV infection radio was higher than the others. The most six common HPV types in this study were HPV 16, 52, 18, 51, 31 and 33.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…In overall summarized of our study found that the HPV prevalence ratio in HSIL was not different from the other in analogous previous studies (Bhatla et al, 2008;Ciapponi et al, 2011;Correnti et al, 2011;Mateos et al, 2011), although the multiple HPV infection radio was higher than the others. The most six common HPV types in this study were HPV 16, 52, 18, 51, 31 and 33.…”
Section: Discussionsupporting
confidence: 44%
“…From a systematic review of seventy-nine studies of type specific HPV prevalence in cervical cancer and high grade lesions from 18 countries in Latin America and the Caribbean (Ciapponi et al, 2011), the results showed 82.5% of HSIL cases harbored in HR-HPV, in which 16.8% (12.9-21.2) was multiple type infection, 45.5% was infected with HPV 16 and 8.9% was HPV 18. The next five most common types were HPV 31, 58, 33, 45 and 52.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neste estudo o HPV 16 também foi o mais prevalente nas mulheres positivas e negativas para o HIV, que tiveram ou não NIC. Infecções cervicais por múltiplos tipos de HPV de alto risco estão associadas com aumento do risco de lesões de alto grau em mulheres com citologia oncótica alterada 38 . As mulheres positivas para o HIV apresentaram, neste estudo, 6,3% de infecções por múltiplos tipos de HPV, porcentagem menor do que os 64,8% encontrados em outros estudos 20,34 .…”
Section: Métodosunclassified
“…En 2008 causó 7,6 millones de defunciones, de las cuales aproximadamente un 70% se produjeron en países de ingresos bajos y medios [1]. El cáncer de cuello uterino es uno de los más frecuentes tanto en incidencia como en mortalidad, contribuye con el 9,8% de todos los cánceres femeninos que afectan a mujeres relativamente jóvenes, y constituye la principal causa de años de vida potencialmente perdidos por cáncer en paí-ses en desarrollo [2,3].…”
Section: Introductionunclassified